2015
DOI: 10.1152/ajpcell.00272.2014
|View full text |Cite
|
Sign up to set email alerts
|

Depressed excitability and ion currents linked to slow exocytotic fusion pore in chromaffin cells of the SOD1G93A mouse model of amyotrophic lateral sclerosis

Abstract: Altered synaptic transmission with excess glutamate release has been implicated in the loss of motoneurons occurring in amyotrophic lateral sclerosis (ALS). Hyperexcitability or hypoexcitability of motoneurons from mice carrying the ALS mutation SOD1(G93A) (mSOD1) has also been reported. Here we have investigated the excitability, the ion currents, and the kinetics of the exocytotic fusion pore in chromaffin cells from postnatal day 90 to postnatal day 130 mSOD1 mice, when motor deficits are already establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 80 publications
(102 reference statements)
1
20
0
Order By: Relevance
“…In a recent study performed to analyse the alterations undergone by the fusion pore in MCCs from wild‐type and in SOD1 G93A transgenic mouse models of ALS, we also found that control CCs stimulated with ACh had a fusion pore kinetics faster than CCs stimulated with K + (Calvo‐Gallardo et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…In a recent study performed to analyse the alterations undergone by the fusion pore in MCCs from wild‐type and in SOD1 G93A transgenic mouse models of ALS, we also found that control CCs stimulated with ACh had a fusion pore kinetics faster than CCs stimulated with K + (Calvo‐Gallardo et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…), and the SOD 1 G93A mouse model of amyotrophic lateral sclerosis carrying the mutation G93A in the enzyme superoxide dismutase 1 (Calvo‐Gallardo et al . ), are also displayed at the bottom.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations